Pelatihan Kepemimpinan Pelatihan “Leadership in Me: Strength to Endure” pada seluruh Pimpinan Divisi dan Unit Kerja RS Siloam Karawaci - Thamrin, Gandadinata (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2023)
A leader must possess the ability to lead and motivate teams, departments, businesses, or organizations to accomplish a task. One method used by businesses or organizations in hiring and promoting individuals is by considering their leadership qualities, as these individuals are seen as valuable assets for the future growth and success of the organization or business. In order for heads of work units at lower levels (unit heads), middle levels (supervisors and head nuns), and upper levels (managers) in all divisions and departments to grow resilient in facing all challenges, problems, threats, and changes from the outside, Leadership in Me: Strength to Endure training or workshops are required, according to the Holistic Care Department. To meet this need, the Siloam Karawaci Hospital Holistic Care Department asked Pelita Harapan University Karawaci lecturers to organize this workshop at Siloam Karawaci Hospital during a gathering for leaders at Siloam Karawaci Hospital. The aim of this workshop is for divisional and departmental leaders at Siloam Karawaci Hospital to improve their leadership skills and high fighting spirit. This workshop activity received a positive response from the workshop participants both in terms of deepening the material, discussion groups and questions and answers and this workshop was also supported by LPPM UPH and provided excellent outputs where participants received additional knowledge and leadership skills that can be applied in their respective divisions and departments. at Siloam Karawaci Hospital.